Development of Storytelling by AI Technology to Enhance Learning Achievement on Loop of Grade 11, Students with Cooperative Learning Method - Srikaew, Oraya; Waree, Jakkrapong (Journal of Computer and Creative Technology, 2025)
This study is experimental research. The objectives of this research were: 1) to develop storytelling by AI technology to enhance learning achievement on loop for grade 11, students. 2) To study the learning achievement of the grade 11, students who study Loop by using storytelling with cooperative learning method. 3) To study the satisfaction of the grade 11, students who study loop by using storytelling with cooperative learning method. The sample group was 20 grade 11, students selected by cluster sampling. The research instruments were 1) storytelling, 2) 2 learning management plans, 3) students' satisfaction assessment form, 4) 20-item achievement test. The research statistics were descriptive, arithmetic means, standard deviation, and paired sample t-test. The research results were: 1. the storytelling had an average rating of 4.80 and an effectiveness of 82.42/ 80.25, exceeding the 75/ 75 criterion. 2. The grade 11, students who were taught science using storytelling with cooperative learning. The result showed a significant improvement in their science test scores after the intervention (p < .05) compared to their pre-test scores. 3. Results of the analysis of students’ satisfaction regarding the direct use of loop with the cooperative learning method with the most intensive use of storytelling. The satisfaction average is 4.53.